1998
DOI: 10.18388/abp.1998_4276
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of polyprenol pattern in leaves of fruit trees belonging to Rosaceae and Cornaceae.

Abstract: The polyprenol pattern in leaves of fruit trees belonging to the Rosaceae (genera: Prunus, Malus) and Cornaceae (genus: Cornus) families is presented. The content of polyprenyl acetates varied within plant species between 10-50 mg per gram of dry weight. In genus Prunus, Cornus and in representatives of species Malus domestica, a mixture of polyprenols composed of 18, 19, 20, 21 isoprene units was found. In six species of genus Prunus (sour-cherry): P. serrulata-spontanea, P. yedoensis, P. fruticosa. P. kurile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The chain length of Dol-P has been shown to be significantly species specific. For example, yeast contains dolichols of 14-17 isoprene units 18 whereas plant possesses dolichols with an isoprene unit of C 19-24 [19][20][21][22] and in mammalian cells the dolichols of 18-21 isoprene units are predominant. 23 The structural difference between the sugar carrier lipids and the bacterial counterpart is the longer prenyl chain and saturation of the α-isoprene unit.…”
Section: Introductionmentioning
confidence: 99%
“…The chain length of Dol-P has been shown to be significantly species specific. For example, yeast contains dolichols of 14-17 isoprene units 18 whereas plant possesses dolichols with an isoprene unit of C 19-24 [19][20][21][22] and in mammalian cells the dolichols of 18-21 isoprene units are predominant. 23 The structural difference between the sugar carrier lipids and the bacterial counterpart is the longer prenyl chain and saturation of the α-isoprene unit.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting IPP serves as a substrate for condensation reactions with different allylic prenyl diphosphates leading to the synthesis of a series of linear prenyl diphosphates of increasing size which, in turn, serve as donors or intermediates in the synthesis of the wide range of plant isoprenoid end products [2]. Among these are long‐chain polyisoprenoid alcohols (polyprenols and dolichols), a family of compounds which have been reported to occur in a number of plants and shown to have a great heterogeneity in terms of carbon chain length [4–7].…”
Section: Introductionmentioning
confidence: 99%
“…To develop high-resolution analysis of polyprenols, a variety of chromatographic conditions were tested. Previously, Swiezewska et al (8) reported a conventional polyprenol separation method using reversed-phase high-performance liquid chromatography (HPLC). Their findings showed that Prunus kurilensis has a broad distribution pattern of polyprenols with two distribution peaks centering at 19 and 34 mers.…”
mentioning
confidence: 99%